The Deformation Structure of the Nuclei 32S and 36Ar - Kharroube, K. A. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
We applied two different approaches to investigate the deformation structures of the two nuclei S32 and Ar36 . In the first approach, we considered these nuclei as being deformed and have axes of symmetry. Accordingly, we calculated their moments of inertia by using the concept of the single-particle Schr dinger fluid as functions of the deformation parameter Î². In this case we calculated also the electric quadrupole moments of the two nuclei by applying Nilsson model as functions of Î². In the second approach, we used a strongly deformed nonaxial single-particle potential, depending on Î² and the nonaxiality parameter Î³ , to obtain the single-particle energies and wave functions. Accordingly, we calculated the quadrupole moments of S32 and Ar36 by filling the single-particle states corresponding to the ground- and the first excited states of these nuclei. The moments of inertia of S32 and Ar36 are then calculated by applying the nuclear superfluidity model. The obtained results are in good agreement with the corresponding experimental data.